Wilhelm von Humboldt and transcultural communication in a multicultural world translating humanity - Walker, John 1956- (Studies in German literature, linguistics, and culture, 2022)
Shows that the work of Wilhelm von Humboldt (1767-1835) forms a philosophy of dialogue and communication that is crucially relevant to contemporary debates in the Humanities